Contribution of physiological and morphological adjustments to drought resistance in two Mediterranean tree species - Serrano, L; Penuelas, J (Biologia Plantarum, 2005)
Plant water potential (ψ), its components, and gas exchange data of two Mediterranean co-occurring woody species (Quercus ilex L. and Phillyrea latifolia L.) were measured in response to seasonal changes in water availability over two consecutive years. The relative contribution of physiological and morphological adjustments to drought resistance was assessed through Principal Component Analyses. There were large adjustments in stomatal conductance (~36 % of accounted variance). Net photosynthetic rate and water use efficiency were closely tuned to water availability and accounted for ~17 % of variance. The slope of the water potential vs. relative water content (dψ/dRWC0) below zero pressure potential increased as a result of seasonal and ontogenic increases in apoplastic water fraction and accounted for ~20 % variance. This tolerance mechanism was accompanied by an increased range of positive pressure potential, suggesting a functional role of sclerophylly in these Mediterranean evergreens. Similarly, changes in the slope of dψ/dRWC in the range of positive pressure potential (~13 % of accounted variance) were associated to variations in cell wall elasticity and resulted in lower RWC at zero pressure potential. When considering the species studied separately, the results indicated the primary role of stomatal regulation in the drought resistance of Q. ilex, while increased apoplastic water fraction had a major contribution in the drought resistance of P. latifolia.
Keywords: Drought stress; net photosynthetic rate; phillyrea latifolia; plant and tissue-water relations; Quercus ilex; Stomatal conductance; water potential